Unmanned Aerial Vehicle Framework for Algae Monitoring - De Almeida, Aline Gabriel [UNESP]; Do Nascimento, Eduardo Vieira; Alvarez, Isaac Gaetani; Kim, Pedro Henrique Correa; Da Rocha, Lidia Gianne Souza; Vivaldini, Kelen Cristiane Teixeira (Institute of Electrical and Electronics Engineers (IEEE), 2021)
Several environmental problems requires constant monitoring to ensure that the human interference is not changing the natural habitats. This kind of effort requires many hours of human labor to be performed manually and has a cost associated with it. This work proposes a framework for managing the UAV tasks of creating routes for scanning and sampling algae overgrowth issues in water bodies and makes a comparison between an offline and an online planning strategy that will be tested in a simulated environment.
Keywords: Coverage path planning; Grid-based coverage; Monitoring; Remote sensing; UAV